Religious Character Internalization through Religious-Based School Activities - Apriyani, Yenti; Kurnianto, Rido; Syam, Aldo Redho; Noh, Mohd Aderi Che (Saneskara: Journal of Social Studies, 2025)
This study aims to examine the process of internalizing students’ religious character through activity-based programs at MI PAS Baitul Qur’an Gontor Ponorogo. The research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. The findings reveal that the internalization of students’ religious character is carried out through several key stages: (1) discipline, by implementing “teng komando” rules, as well as a system of punishment and reward; (2) habituation, through daily routines such as congregational prayers, Qur’an memorization (tahfidz), and the 6S culture (smile, greet, salute, polite, and ready); (3) exemplary practice, by positioning teachers and all school stakeholders as role models who consistently demonstrate positive behavior; and (4) creation of a conducive environment, supported by adequate facilities and educational media such as “talking walls” and consistent enforcement of discipline among all school members. The novelty of this study lies in demonstrating that an activity-based internalization process significantly shapes students’ religious character. The outcomes include improved discipline in daily life, enhanced independence in various activities, the development of politeness in behavior and communication, the practice of honesty in interactions, and a stronger sense of personal responsibility.